Asymmetric responses of resource use efficiency to previous‐year precipitation in a semi‐arid grassland. (5th February 2021) - Han, Juanjuan; Chen, Jiquan; Shi, Weiyu; Song, Jian; Hui, Dafeng; Ru, Jingyi; Wan, Shiqiang
Abstract: Intensified inter‐annual fluctuations in precipitation could profoundly impact terrestrial ecosystems. However, how changes in previous‐year precipitation influence current ecosystem functioning (e.g. resource use efficiency) in semi‐arid regions remains unclear. In this study, water use efficiency (WUE) and light use efficiency (LUE) were investigated in a multi‐year precipitation gradient experiment with seven treatment levels: 20%, 40% and 60% decreases and 20%, 40% and 60% increases in the amount of natural rainfall plus ambient precipitation. Plots receiving 60% less precipitation were representative of extreme dry years, whereas the other treatment levels fell within the normal year‐to‐year range in precipitation change. Measurements made in both the post‐treatment period (2013–2015) and the treatment period (2010–2012) provided an opportunity to quantify the legacy effects of precipitation on resource use efficiency (RUE). Sensitivities of LUE to previous‐year precipitation were not changed among treatments in 2013. However, asymmetric responses of RUEs (i.e. WUE and LUE) to previous‐year precipitation were found in 2014–2015. WUE2014, WUE2015, LUE2014 and LUE2015 responded more strongly to previous normal decreased than increased precipitation. Importantly, they were more sensitive to previous extreme dry year (represented by 60% precipitation reduction) than normal wet year (represented by 60% precipitation increment). Above‐ground net primary productivity (ANPP) rather than resource absorption ( R uptake ) drove these asymmetric responses of RUE, and biomass of grasses further explained the asymmetric responses of ANPP. This study reveals the nonlinear responses of RUE to previous‐year precipitation and highlights that the legacy effects of precipitation on RUE can be ascribed to the changes in vegetation composition. Our findings can facilitate the prediction of the legacy effects of precipitation variation on grassland ecosystem functions in the future. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.